การสังเคราะห์ไตรเมทิลอลโพรเพนเอสเทอร์บนตัวเร่งปฏิกิริยาโลหะออกไซด์ผสม - สุรพจน์ เกตุคง (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The present thesis studied the preparation of catalyst for synthesis of trimethylolpropane esters via transesterification. The catalyst was prepared by doping KF on Mg-Al layer double hydroxide calcined at 500 ℃ as supported catalyst (KF/HTC-500). KF/HTC – 500 was characterized by X-ray diffraction (XRD), thermogravimetric/ differential thermal analysis (TG/DTA), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), Hammett titration method, N₂ adsorption-desorption measurement and temperature-programmed desorption of CO₂ (CO₂-TPD). The results showed that the KF/HTC – 500 calcined at 500 ℃ (KF/HTC-500(500)) showed high basicity due to the presence of active sites such as Mg-Al mixed oxide, K₂O, KMgF₂, O²⁻ and F. Moreover, this catalyst showed high specific surface area and porosity. Unlike homogeneous catalysis, using KF/HTC-500(500) in the synthesis of trimethylolpropane did not produce soap in the product mixture. The suitable conditions for the synthesis of C₈-C₁₀ trimethylolpropane esters (C₈-C₁₀ TMP esters) and C₁₂-C₁₄ trimethylolpropane esters (C₁₂-C₁₄ TMP esters) using KF/HTC-500(500) were the molar ratio of FAME:TMP; 3.5:1, amount of catalyst; 5 wt.% temperature; 170 ℃, time; 8 hand under N₂ flow. These conditions gave the highest C₈-C₁₀ FAME conversion of 99.9 wt.% and trimester yield of 81 wt.%.